(3GdJYQja HeG CfSJ GdgLQI ef eYGde OGQ GdgLQIs - (3eMeO Hf CMeO Hf eMeO Hf Nda GdNRQLj GdCfUGQj GdSYOj GdeOfj, CHh YHO Gddg ,LeGd GdOjf GdeWQj,J (B741 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa WjHI GdWjHI HMdhd eUWaGg hHYO aEf GdYfGjI HGdeOjfI GdTQjaI eJYjfI s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3ef Hfi ddg HjJkG Hfi ddg dg HjJkG ai GdLfI hGdMeO ddg QH GdYGdejf MSHfG Gddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3Hg JJeI eSLO QShd Gddg Udi Gddg Ydjg hSde ai CQHY hQbGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs